Implementasi Kurikulum Merdeka pada Mata Pelajaran Akidah Akhlak di MAN 2 Kota Kediri - Anggun Akmila; A. Jauhar Fuad (JOM, 2025)
The Merdeka Curriculum is an innovation in education that emphasizes freedom and independence for students in the learning process. The implementation of the Merdeka Curriculum is important to support the achievement of educational goals, including in the teaching of Aqidah Akhlak. This curriculum provides space for teachers to develop more flexible, student-centered learning. The purpose of this study is to analyze how the Merdeka Curriculum is implemented in the subject of Akidah Akhlak. This study uses a qualitative approach and descriptive analysis method. The results of the study show that the implementation of the Merdeka Curriculum begins with planning, which consists of developing an Operational Curriculum for the Education Unit, participating in training, analyzing CP, TP, ATP, and actualizing them in the creation of teaching modules. The next stage is implementation, which has been realized in accordance with the teaching modules by carrying out several stages, such as introduction, core, and conclusion. The evaluation or assessment of the independent curriculum in the subject of faith and morals consists of formative and summative assessments. There are problems experienced by schools in implementing the independent curriculum, such as the uneven abilities of teachers and dependence on technology. Despite facing several challenges, the implementation of the Independent Curriculum at MAN 2 Kota Kediri is running quite well and effectively. Therefore, the success of implementing the Merdeka Curriculum in Akidah Akhlak learning is largely determined by the ability of teachers to design and implement learning in accordance with the curriculum requirements.